Application of William's Flexion Exercise in Patients with Low Back Pain Problems: A Literature Review - Amien Akbar; Ricky Zainuddin (Journal La Medihealtico, 2020)
This article aims to review the application of William's Flexion exercise in patients with low back pain problems. Low back pain is a clinical syndrome with the main symptoms of pain or discomfort in the lower back region which until now about 23% of adults in the world experience it. One of the physical therapies that can be used to treat patients with low back pain is William's flexion exercise which has been used for years and has been proven to relieve or relieve pain in patients with low back pain. This literature review aims to analyze the effect of applying William's Flexion exercise to patients with low back pain problems. Methods: This study explores quantitative evidence published in electronic databases such as Pubmed, and Google Scholar. Using a search strategy, we identified 32 articles with potential and relevant to the research objectives, but in this literature we only reviewed 5 articles. Results: We can see a significant effect on reducing the pain scale experienced by respondents after being given William's flexion exercise intervention. Conclusion: The results of a review of several articles in this review literature concluded that William's Flexion Exercise program was proven to be effective in reducing pain scales in patients with low back pain problems.